Horse owners seeking online health information: a mixed-methods study - Haase, Laura; Winter, Julia; Grummt, Sophia; Sedlmayr, Martin; Sedlmayr, Brita (Frontiers in Veterinary Science, 2025)
BackgroundMany people seek health-related information online, not only for themselves but also on behalf of others who cannot articulate their symptoms. This proxy information-seeking behavior is particularly relevant for animal owners, who must interpret their animals’ symptoms without direct verbal feedback. While online health information-seeking in the context of one’s own health is well-studied, the specific challenges of searching by proxy, especially for animal health information, remain largely unexplored.ObjectiveThis study aimed to determine the specific information needs and search behavior of animal owners. As a case study, horse owners were selected, representing a group regularly searching the web for health-related advice concerning their animals.MethodsA mixed-methods approach was used with 17 horse owners in Germany. Participants first described a recent search for equine health information. They were then shown a video of a horse experiencing an asthma attack and asked to conduct a search on how to proceed with the horse’s condition. Afterwards, they were questioned about their respective search behavior.ResultsThe participants’ main initial questions revolved around the cause of the horse’s condition, its urgency of veterinary treatment and the cost of treatment. All participants chose the Google search engine as the starting point for their search and formulated an average of 3.71 (SD: 2.02) queries. Each of these queries contained an average of 3.81 words (SD: 1.57). Most searches (52%) were evidence-directed with 29% using multiple descriptors of the horse’s situation. An average of 0.97 results (SD: 1.38) were clicked per query, with titles containing all search terms in 13% of cases. Participants reported experiencing several barriers to their search, including difficulties in formulating precise queries and the need for additional guidance during the search process.ConclusionThe findings highlight the need for improved online information systems, offering better guidance, context-aware search support, and trustworthy sources. The insights could inform veterinarians on how to better address their clients’ communication and information needs, provide them with the skills and knowledge they need to conduct online research and therefore build a better animal health partnership with them.